2019
DOI: 10.1186/s12914-019-0186-6
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between depression and sexual health service utilization among men who have sex with men (MSM) in Côte d'Ivoire, West Africa

Abstract: Background In Cote D’Ivoire, there has been limited coverage of evidence-based sexual health services specifically supporting men who have sex with men (MSM). To date, there has been limited study of the determinants of engagement in these services including multiple intersecting stigmas and depression. Methods 1301 MSM aged 18 years and older, were recruited using respondent-driven sampling in Abidjan, Yamoussoukro, Gagnoa and Bouake, Cote d’Ivoire from January 2015 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 78 publications
1
13
0
Order By: Relevance
“…Many studies have con rmed that the generation of feelings of entrapment and defeat may trigger depression and lead to poor psychological states such as lack of selfesteem and self-con dence [3,6,7,31]. Therefore, this study used the PHQ-9 to assess depressive symptoms among MSM, consistent with previous studies [32,33]. The internal consistency reliability (Cronbach's α coe cient) of the PHQ-9 in this study was 0.874.…”
supporting
confidence: 78%
“…Many studies have con rmed that the generation of feelings of entrapment and defeat may trigger depression and lead to poor psychological states such as lack of selfesteem and self-con dence [3,6,7,31]. Therefore, this study used the PHQ-9 to assess depressive symptoms among MSM, consistent with previous studies [32,33]. The internal consistency reliability (Cronbach's α coe cient) of the PHQ-9 in this study was 0.874.…”
supporting
confidence: 78%
“…Many studies have confirmed that the generation of entrapment and defeat may trigger depression and lead to poor psychological states such as lack of self-esteem and self-confidence [ 5 , 8 , 9 , 37 ]. Therefore, this study used the PHQ-9 to assess depressive symptoms among MSM, consistent with previous studies [ 38 , 39 ]. The internal consistency reliability (Cronbach’s α coefficient) of the PHQ-9 in this study was 0.874.…”
Section: Methodsmentioning
confidence: 66%
“…Our data suggest an association between depression, viral non-suppression and an increased risk of STIs. This potentially represents a robust target for intervention as only 10% of persons living in Sub-Saharan Africa have adequate access to mental health care [31]. Integrating care, such as mental health services and behavioral counseling for STI prevention, may be an effective and cost-effective intervention to reduce STIs [32].…”
Section: Discussionmentioning
confidence: 99%